Combination of simultaneous saccharification and fermentation of corn stover with consolidated bioprocessing of cassava starch enhances lipid production by the amylolytic oleaginous yeast Lipomyces starkeyi. (November 2022) - Zhao, Man; Zhou, Wenting; Wang, Yanan; Wang, Jian; Zhang, Junlu; Gong, Zhiwei
Graphical abstract: Highlights: Combination of SSF of corn stover with CBP of cassava starch was firstly developed. The combination strategy showed synergistic effect for improving lipid production. Rapid hydrolysis of starch into fermentable sugars eliminated a pre-hydrolysis step. The enzyme cost could be significantly decreased via the combination strategy. Biodiesel from the combination strategy showed high-quality fuel properties. Abstract: Highly integrated processes are crucial for the commercial success of microbial lipid production from low-cost substrates. Here, combination of simultaneous saccharification and fermentation (SSF) of corn stover with consolidated bioprocessing (CBP) of cassava starch by Lipomyces starkeyi was firstly developed as a novel strategy for lipid production. Starch was quickly hydrolyzed within 24 h by the amylolytic enzymes secreted by L. starkeyi to provide adequate fermentable sugars at the initial stage of culture, which eliminated the pre-hydrolysis step. More interestingly, synergistic effect for achieving higher lipid production by combined utilization of corn stover and cassava starch at relatively low enzyme dosage was realized, in comparison with the separate utilization of these two substrates. The fatty acid profiles indicated that lipid prepared by the combination strategy was suitable precursor for biodiesel production. The combined SSF&CBP strategy offers a simplified, highly-efficient, and economical route for co-valorization of low-cost substrates into lipids.